SEMANTIC AND COLLOCATIONAL ASYMMETRIES IN ENGLISH AND UZBEK SYNONYMIC UNITS (Eureka Journal of Humanities and Social Research, 2026)
This study investigates semantic and collocational asymmetries in English and Uzbek synonymic units from a comparative and contrastive linguistic perspective. The research focuses on how synonymic relations in the two languages differ in terms of semantic structure, contextual usage, collocational compatibility, stylistic differentiation, and pragmatic force. The study employs comparative, semantic, componential, contextual, and corpus-based analytical methods in order to identify similarities and divergences between English and Uzbek synonymic series. The findings demonstrate that synonymic equivalence between the two languages is predominantly partial rather than complete. Many lexical items share a common denotative core while differing significantly in connotation, register, collocational behavior, and communicative function.
Keywords: synonymy, semantic asymmetry, collocational analysis, comparative lexicology, English linguistics, Uzbek linguistics, lexical semantics, translation equivalence, corpus linguistics, pragmatic meaning